A mindful eating program improved home eating environment and reduced food insecurity among rural economically marginalized families - Jiying Ling; Nagwan Zahry; Sisi Chen; Yingcen Xie; Hannah Lalonde; Lorraine B. Robbins; Jean M. Kerver (Critical Public Health)
To address the urban-rural and socioeconomic disparities in childhood obesity, this study evaluated a childcare-based mindful eating intervention on improving eating behavior and home eating environment and reducing obesity and food insecurity among economically marginalized families in rural areas. A one-group pragmatic trial with a pretest-posttest design was conducted across 26 childcare classes in rural Midwestern U.S. Trained childcare teachers delivered a 14-week mindful eating intervention to preschoolers, consisting of one 20-minute session per week. Mixed-effects models were used to adjust for childcare center and classroom random effects. Two hundred preschoolers (mean age = 47.69 months, 50% female, 7.5% Hispanic) and 192 caregivers (mean age = 32.19 years, 96.4% female, 4.7% Hispanic) participated. One third caregivers were single, and 43.2% were unemployed. Household food insecurity rate decreased from 51% to 36% (p < .001). Home eating environment improved significantly. Preschoolers’ baseline weight status significantly modified the effects on BMI z-score (p = .044). Preschoolers who had overweight or obesity at baseline experienced an average decrease of 0.20 in their BMI z-score. Results support the promising effects of the intervention on improving home eating environment and reducing childhood obesity and food insecurity.